2007
DOI: 10.1093/aob/mcm130
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cambial Reactivation by Localized Heating in a Deciduous Hardwood Hybrid Poplar (Populus sieboldii x P. grandidentata)

Abstract: The results suggest that, in deciduous diffuse-porous hardwood poplar growing in a temperate zone, the temperature in the stem is a limiting factor for reactivation of phloem and cambium. An increase in temperature might induce the conversion of storage starch to sucrose for the activation of cambial cell division and secondary xylem. Localized heating in poplar stems provides a useful experimental system for studies of cambial biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
3
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 22 publications
(47 reference statements)
5
92
3
5
Order By: Relevance
“…Our observations are in contrast with previous fi ndings of similar experiments with elevated temperature carried out by other scientists on different tree species (Abies sachalinensis, Larix leptolepis, Cryptomeria japonica, Populus sieboldii x P. grandidentata) (e.g., Oribe and Kubo, 1997;Oribe et al, 2001Oribe et al, , 2003Begum et al, 2007Begum et al, , 2010. However, in their cases the selected trees were either relatively young (12-40 years old) or they were exposed to elevated temperatures only for a short period of time (i.e., one month).…”
Section: Diskusijacontrasting
confidence: 99%
See 3 more Smart Citations
“…Our observations are in contrast with previous fi ndings of similar experiments with elevated temperature carried out by other scientists on different tree species (Abies sachalinensis, Larix leptolepis, Cryptomeria japonica, Populus sieboldii x P. grandidentata) (e.g., Oribe and Kubo, 1997;Oribe et al, 2001Oribe et al, , 2003Begum et al, 2007Begum et al, , 2010. However, in their cases the selected trees were either relatively young (12-40 years old) or they were exposed to elevated temperatures only for a short period of time (i.e., one month).…”
Section: Diskusijacontrasting
confidence: 99%
“…On the other hand, heating did not stimulate cell division in cambium before regular cambial activity in the deciduous Larix leptolepis, which appeared only after the activation of buds (Oribe et al, 2001). Cambial reactivation in Populus sieboldii x P. grandidentata occurred before bud burst, indicating their independence of each other (Begum et al, 2007). Begum et al (2010) reported that cambial sensitivity from late winter to early spring under natural conditions and in locally heated stems of Cryptomeria japonica might depend both on cambial age and the stage of cambial dormancy.…”
Section: Diskusijamentioning
confidence: 87%
See 2 more Smart Citations
“…In natural stands, the onset of cambial activity occurs within a relatively narrow range of daily minimum air temperature (+2 to +7°C in 80% of the data; Rossi et al 2008), resulting in altitudinal gradients of cambium resumption (Moser et al 2010;Oladi et al 2010;Prislan et al 2013). Moreover, the resumption of cambial activity can be triggered during late winter by an artificial heating of tree stems (Oribe et al 2003;Begum et al 2007Begum et al , 2010. Interestingly, this artificial resumption of cambial activity can only be triggered during the ecodormancy phase of cambium tissue (referred to as the "quiescent phase" in Oribe and Kubo 1997;Begum et al 2013) after the chilling requirement has been fulfilled during endodormancy (referred to as the "rest phase" in Little and Bonga 1974;Begum et al 2013).…”
Section: The Phenology Of Wood Formationmentioning
confidence: 99%